Improving Significantly: Enhancing Elementary Science Literacy through STEM-PjBL Web-Based Learning Media - Balgis Janah; Ika Lestari; Firmanul Catur Wibowo (Edunesia : Jurnal Ilmiah Pendidikan, 2026)
This study developed B-Science, a STEM-PjBL web-based learning medium designed to improve fifth-grade students’ science literacy on the human digestive system and water cycle. The research employed Research and Development using the Hannafin and Peck model, consisting of need assessment, design, and development–implementation phases. The participants were 31 fifth-grade students at SDN Balimester 06, East Jakarta. Data were collected through expert validation, student response questionnaires, and pretest–posttest science literacy tests. Results showed that material, language, and media validation reached 90.75%, indicating very feasible quality. Student trials also produced highly positive responses above 92%. The effectiveness test showed normal data distribution, a significant difference between pretest and posttest scores, and a high N-gain of 0.76. These findings indicate that B-Science is valid, practical, and effective for strengthening elementary students’ science literacy through interactive visualization and structured project-based learning. It also supports collaborative inquiry and self-paced access via mobile devices and browsers.